Branched alkylated polynorbornene and 3D flower-like MoS2 nanospheres reinforced phase change composites with high thermal energy storage capacity and photothermal conversion efficiency. (December 2021) - Cao, Yufeng; Fan, Dongli; Lin, Shaohui; Ng, Flora T.T.; Pan, Qinmin
Abstract: Form-stable phase change materials (FSPCMs) have a great attraction for relieving the contradiction of energy consumption and environmental pollution. However, the practical effects of FSPCMs are severely compromised by their intrinsic drawbacks including liquid leakage, inferior cycling durability and lacking light to heat conversion ability, etc. In this paper, we have constructed a group of novel composite FSPCMs with high latent heat storage density, enhanced thermal stability and excellent cycling life, using 1-octadecanol (OCC) as the latent heat storage units and the branched alkylated polynorbornene as well as 3D flower-like MoS2 nanospheres as the supporting scaffolds for the composite FSPCMs. The branched alkylated polynorbornene enhances the toughness of the composites under the induced dipole force among their alkyl chains so that the liquid leakage during the phase transition can be minimized or completely circumvented. Furthermore, 3D flower-like MoS2 nanospheres, as a photothermic absorbent, impart the composite FSPCMs with enhanced light to thermal conversion efficiency (85.5%), promising for a potential application in conversion and storage of solar energy. Graphical abstract: Image 1